2018
DOI: 10.3766/jaaa.16017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early- and Late-Arriving Room Reflections on the Speech-Evoked Auditory Brainstem Response

Abstract: The stimuli that are acoustically most similar (direct and early) result in electrophysiological responses that are not significantly different, whereas the stimuli that are acoustically most different (direct and late, early and late) result in responses that are significantly different across all response measures. These findings provide insights toward the understanding of the effects of the different components of the RIRs on auditory processing of speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…(2011), and Song, Skoe, et al. (2011) found no effects of background noise on any of their sustained EFR measures (including F0), while AlOsman, Giguère, and Dajani (2016) found that background noise enhanced F0 amplitudes of their sustained EFRs. Results from this study and from Jenkins et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(2011), and Song, Skoe, et al. (2011) found no effects of background noise on any of their sustained EFR measures (including F0), while AlOsman, Giguère, and Dajani (2016) found that background noise enhanced F0 amplitudes of their sustained EFRs. Results from this study and from Jenkins et al.…”
Section: Discussionmentioning
confidence: 94%
“…(2018) indicate that the addition of background noise does not have the same effect on speech-ABRs recorded from individuals with SNHL as it does on individuals with normal hearing. It should be noted that the SNR of +10 dB that we used to collect speech-ABRs in noise is the same SNR that was used in the earlier referenced studies on individuals with normal hearing (with the exception of the 0 dB SNR used in AlOsman et al., 2016); therefore, the SNR does not explain differences between speech-ABRs in noise in individuals with normal hearing and individuals with SNHL. One explanation may be the increase in excitatory and reduction in inhibitory patterns in the inferior colliculus that occurs with SNHL as reported by Vale and Sanes (2002) in their study on deafened gerbils.…”
Section: Discussionmentioning
confidence: 99%
“…Li and Jeng (2011) also found that F 0 of the FFR did not decrease in amplitude with positive dB SNR levels; it was only affected at 0 dB SNR and negative dB SNR levels. While AlOsman et al (2016) and Prévost et al (2013) found an enhancement in FFR F 0 in background noise compared with in quiet, AlOsman et al stipulated that this enhancement was modulated by top-down processing to improve speech understanding in background noise, while Prévost et al attributed this enhancement to the phase locking to the stimulus envelope of auditory nerve fibers that are further away from the characteristic frequency of F 0 , in order to compensate for the effect of background noise. Involvement of the auditory cortex in the FFR has been shown by Coffey et al (2016) in their FFR and magnetoencephalography study where auditory cortical activation at F 0 of the stimulus was found in normal-hearing adults.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, auditory neuroscience has progressively shifted to the use of speech stimuli (e.g. vowels, consonant vowels, and words) [3], [6], [7], [4], [8]. ABR is typically measured in an anechoic audiometric room using a three electrodes setup where a recording electrode is placed at the vertex, a reference electrode on the right ear lobe, and the ground electrode on the left ear lobe [3].…”
Section: Introductionmentioning
confidence: 99%
“…EFR and FFR diagrams are shown in Figure 2. Several studies have reported that the EFR and FFR correlate with long-term experience with music or tonal language [10], [11], the ability to understand speech in the presence of background noise, [12], [6], [13] and reverberation [14]- [16]. As mentioned above, the analysis and interpretation of the transient ABR involves identifying the response waveforms and then measuring their amplitudes and latencies against normative data [3].…”
Section: Introductionmentioning
confidence: 99%